‘It's all the way you look at it, you know’: reading Bill ‘Bojangles’ Robinson's film career - Durkin, Hannah (Routledge, 2012)
This paper engages with a major paradox in African American tap dancer Bill ‘Bojangles’ Robinson's film image – namely, its concurrent adherences to and contestations of dehumanising racial iconography – to reveal the complex and often ambivalent ways in which identity is staged and enacted. Although Robinson is often understood as an embodiment of popular cultural imagery historically designed to dehumanise African Americans, this paper shows that Robinson's artistry displaces these readings by providing viewing pleasure for black, as much as white, audiences. Robinson's racially segregated scenes in Dixiana (1930) and Hooray for Love (1935) illuminate classical Hollywood's racial codes, whilst also showing how his inclusion within these otherwise all-white films provides grounding for creative and self-reflexive artistry. The films' references to Robinson's stage image and artistry overlap with minstrelsy-derived constructions of ‘blackness’, with the effect that they heighten possible interpretations of his cinematic persona by evading representational conclusion. Ultimately, Robinson's films should be read as sites of representational struggle that help to uncover the slipperiness of performances of African American identities in 1930s Hollywood.